PURCAHASE DECISION OF KOI FISH ASSESSED FROM PARENT QUALITY, HEALTH AND SOCIAL MEDIA - Siti Maryam; Rifi Ardiansah; Fitri Setya Marwati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to analyze the simultaneous and partial effect of broodstock quality, fish health and social media on purchasing decisions for koi fish at Merapi Koi Farm, Magelang Regency. This type of research is descriptive quantitative. The population is all consumers who purchase koi fish at Merapi Koi Farm, Magelangzdistrict with anzunknownzamount. Thezsampel is 100zcustomers. Whozbuys ornamentalzkoi fish at Merapi Koi Farm. Datazobtained from azquestionnairezwith a samplingztechniquezpurposivezsampling. The datazanalysis technique used iszmultiplezlinear regressionzanalysis. The resultszof the F test provezthat the quality ofzbroodstock,zfish healthzand socialzmedia simultaneouslyzaffectzthe purchasingzdecisionzfor ornamental koi fish at Merapi Koi Farm, Magelang Regency, where the value Fhitung is 49,713 > Ftabel which is as big 2,70 with significance 0,000 whichzmeans